Label-Free High-Density Mapping Reveals Sustained Reentrant Activity in iPSC-Derived Atrial Cardiomyocytes from Brugada Syndrome Patients - Li, Wener; Congur, Irem; Binnewerg, Björn; Schubert, Mario; Luo, Xiaojing; Schmidt, Sabine; Dzekhtsiarova, Yuliya; Tao, Wenjing; Bulst, Martin; Wegner, Sebastian; Jahnke, Heinz-Georg; Guan, Kaomei (浪淘沙预印本平台, 2026)
Atrial fibrillation (AF) is unexpectedly prevalent in Brugada syndrome (BrS), yet the mechanisms linking SCN5A loss-of-function to atrial instability remain elusive. Here, we combined patient-specific induced pluripotent stem cell-derived atrial cardiomyocytes with label-free high-density microelectrode array (HD-MEA) mapping. We show that SCN5A haploinsufficiency creates an arrhythmogenic substrate driven by the concomitant loss of excitability and heterogeneous Cx40 remodeling. This specific architecture renders mutant atrial syncytia highly susceptible to sustained, high-frequency spontaneous micro-reentry, a reentry-in-a-chip phenotype not recapitulated by pharmacological sodium-channel blockade in controls. Notably, genotype-negative BrS lines lacked spontaneous instability, exhibiting only inducible arrhythmia. Pharmacological profiling demonstrated that rhythm-control agents terminated reentry, whereas rate-control agents solely slowed rotation. This study defines the first human in vitro model of spontaneous atrial reentry, distinguishing primary mutation-driven defects from secondary clinical remodeling and providing a precision platform for anti-arrhythmic drug discovery.